Optimal Scheduling Strategy for Regional Microgrid considering Large-Scale Access of Electric Vehicles. (22nd September 2022) - Zhang, Tengfei; Cheng, Yiling; Peng, Chen; Ma, Fumin; Zeng, Deliang; O'Hare, Gregory M. P.
Abstract : In recent years, renewable energy, especially photovoltaic (PV) generation, has been widely applied in commercial and residential areas, forming the structure of regional microgrids (MG). On the other hand, as large-scale electric vehicles (EVs) are connected to the regional MG, their disordered charging and discharging will enable extremely bad effects. However, most of the existing scheduling strategies focused on a single MG or considered the MG as a single node, ignoring the characteristics of different subareas. To address these limitations, we propose an optimal scheduling strategy considering large-scale access of EVs based on the typical regional MG composed of commercial and residential subareas, combining the power consumption characteristics of the two subareas and the travel characteristics of EVs. This strategy is mainly to dynamically adjust the charging and discharging of EVs in each subarea, combined with the real-time deployment of excess PV energy, so as to realize the overall scheduling of the regional MG. Numerical results show that EVs store electric energy during valley hours and output electric energy during peak hours. Furthermore, compared with no scheduling method, the proposed strategy reduces the whole-day electricity bills of the regional MG.